Formation Of Collaborative Skills Of Students Based On Multi-Vector Pedagogical Approaches In Higher Education (Eurasian Journal of Learning and Academic Teaching, 2024)
The concept of multi-vector in the education system, approaches to the creation of a multi-vector model for improving the qualifications of education workers are analyzed. Based on the analysis, an image of a new multi-vector system of additional professional education, built on the basis of a professional standard for a teacher, is proposed.